Characterising physical habitat at the reach scale: River Tern, Shropshire - Harvey, Gemma (2006)
Characterisation of the complex geomorphological and ecological structure of river channels into workable units of instream habitat is a key step in enabling the assessment of habitat for river management purposes. The research presented in this thesis uses a range of methodological approaches at a variety of spatial scales in order to improve the conceptual basis of habitat characterisation at the reach and sub-reach scale. An appraisal of published works is used in conjunction with an extensive analysis of habitat features for sites across the UK, and intensive field studies on the River Tern, Shropshire, to improve the conceptual basis and ecological validity of the 'physical biotope' as the basic unit of instream habitat. Physical biotopes demonstrate correlations with biologically functional habitat units at relatively broad scales, suggesting that assemblages of habitat units may provide the most appropriate level of simplification of aquatic habitat structure. A simplified, but more transferable classification using biotope assemblages is suggested, with potential application to a range of instream assessment and river design needs. Reach-scale field surveys reveal complex and dynamic relationships between channel hydraulics and morphology and highlight the influence of sampling design and hydrological context on the outcomes of rapid field surveys. A microscale research component addresses within-biotope variation at small scales by focusing on high frequency flow behaviour and sediment transport mechanisms which have, to date, been largely overlooked in biotope studies. This provides both detailed descriptions of hydraulic behaviour, and an indication of differences in internal spatial and temporal heterogeneity between biotopes, with implications for instream biota.